EFFECT OF OXYTOCIN AND BROMOCRIPTINE ON CORPORA LUTEA AND PSEUDOPREGNANCY IN MICE - A. S. AL- Khadi, N.; S. AL- Janabi, A.; A. J. Flaih, A. (The Iraqi Journal of Veterinary Medicine, 1990)
Oxytocin adminstered on the fifth day of pseudopregnancy daily at a dose of 200 mU for 4 days, caused. an extension in pseudopregnancy length. Concomitant adminstration of bromocriptine (10 mg) caused reduction in pseudopregnancy length. Ovarian and uterine changes associated with oxytocin adminstration included: an increase in weight and percentage of active corpora lutea in animals sacrificed 48 and 72 hours post treatment.